2016
DOI: 10.1089/cyber.2016.0134
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Internet-Based Professional Social Networking and Emotional Distress

Abstract: Professional social networking websites are commonly used among young professionals. In light of emerging concerns regarding social networking use and emotional distress, the purpose of this study was to investigate the association between frequency of use of LinkedIn, the most commonly used professional social networking website, and depression and anxiety among young adults. In October 2014, we assessed a nationally representative sample of 1,780 U.S. young adults between the ages of 19-32 regarding frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Table 1 outlines, to the best of our knowledge, the only three studies that associate either anxiety or depressive feelings with professional SNS usage, such as LinkedIn and Xing. Two of these studies support the idea that professional SNSs can induce depression and anxiety through social comparison, similar to general SNSs (Jones et al, 2016; Ozimek & Bierhoff, 2020). In contrast, Wang et al (2023) found that information overload experienced from viewing content on professional SNSs increases workplace anxiety.…”
Section: Introductionsupporting
confidence: 56%
“…Table 1 outlines, to the best of our knowledge, the only three studies that associate either anxiety or depressive feelings with professional SNS usage, such as LinkedIn and Xing. Two of these studies support the idea that professional SNSs can induce depression and anxiety through social comparison, similar to general SNSs (Jones et al, 2016; Ozimek & Bierhoff, 2020). In contrast, Wang et al (2023) found that information overload experienced from viewing content on professional SNSs increases workplace anxiety.…”
Section: Introductionsupporting
confidence: 56%
“…It may be that how one feels in response to social media (ie, Instagram’s image-based or LinkedIn’s professional content) may cause dissatisfaction with oneself and subsequent depressive symptoms. 36,8791…”
Section: Discussionmentioning
confidence: 99%
“…From the 2,885 people who took part in voting on LinkedIn, there were 62% of people who stated that they experienced LinkedIn Fatigue, namely experiencing mental fatigue, feeling anxiety that leads to FOMO, the desire to do work excessively or workaholic, feeling guilty at rest and making themselves feel inferior because they compare yourself with the achievements of others ( [17]; [18]). In a study conducted in 2016 of 1,780 participants, 292 of them used LinkedIn once a week, participants who use LinkedIn have a much greater chance of developing depression than those who do not use LinkedIn, the overall relationship between LinkedIn users and depression is that they have a more significant chance of increasing anxiety [19]. Feeling of fear, anxiety and worry can make it difficult for individuals to master the environment, establish positive relationships and accept themselves, which are important aspects of psychological well-being [20].…”
Section: Icap-hmentioning
confidence: 99%